Hierarchical self-assembly of a reflectin-derived peptide - Dias, Ana Margarida Gonçalves Carvalho; Moreira, Inês Pimentel; Lychko, Iana; Lopes Soares, Cátia; Nurrito, Arianna; Moura Barbosa, Arménio Jorge; Lutz-Bueno, Viviane; Mezzenga, Raffaele; Carvalho, Ana Luísa; Pina, Ana Sofia; Roque, Ana Cecília Afonso (Frontiers in Chemistry, 2023)
Reflectins are a family of intrinsically disordered proteins involved in cephalopods camouflage, making them an interesting source for bioinspired optical materials. Understanding reflectins assembly into higher-order structures by standard biophysical methods enables the rational design of new materials, but it is difficult due to their low solubility. To address this challenge, we aim to understand the molecular self-assembly mechanism of reflectins basic unit - the protopeptide sequence YMMSGYQ, as a means to understand reflectins assembly phenomena. Protopeptide self-assembly was triggered by different environmental cues, yielding supramolecular hydrogels, and characterized by experimental and theoretical methods. Protopeptide films were also prepared to assess optical properties. Our results support the hypothesis for protopeptide aggregation model at an atomistic level, led by hydrophilic and hydrophobic interactions mediated by tyrosine residues. Protopeptide-derived films were optically active, presenting diffuse reflectance in the visible region of the light spectrum. Hence, these results contribute to a better understanding of the protopeptide structural assembly, crucial for the design of peptide and reflectin based functional materials.